Scientific realism and human emancipation - "Bhaskar,Roy" (London, 1987)
In a wide ranging survey of the minefields of contemporary philosophy and social thought, Roy Bhaskar develops his own positive and highly original theories of the nature of science and being, social science and history and philosophical discourse and ideology.